Interpretation, Imagination, and Transformation in the Creation of the “Timang XekorY” - Laura Pranti, Tutom; Shanthi, Nadarajan; Yoesbar, Djaelani (Human Resource Management Academic Research Society, 2022)
This study is about the creation of the XekorY composition (by Laura Pranti Tutom), that aims to visualize the traditional Iban invocation ritual of Timang Tuah (Goodluck chant). This exploratory study recounts from the first person perspective, the process in bringing to life creativity from three different levels: interpretation, imagination and transformation, before a live audience at Sultan Idris Education University on 24th of May, 2019. This paper narrates through music and visual artistry, the journey and experience of the lemambang (bards) on a mission to deliver the Timang Tuah. For interpretation, the content is summarized from a chanting text and conceptualized through the composer’s inspirational framework, ideas and imagination. The imagination has been transformed into a musical performance created through a combination of 4D (luck based numbers) and XY coordinates, followed by a series of pitch. The data include field data collected from questionnaires, semi structured interviews and participant observation involving bards, community leaders, ritual specialists, and students from the Music program from UPSI and UNIMAS. The findings suggest that most students (88%) who participated as music players and audience of the Timang XekorY performance could understand and appreciate the creative effort and were willing to watch the “real” Timang Tuah performance, while members of the public who had limited musical knowledge benefited from the Program Book of the Timang XekorY distributed before the performance.